Computerized registration system 2.0 - Carreon, Jesus Felipe M. (2003)
Automation is thought to be the panacea for most tedious manual processes. However, automation, similar to upgrading computer systems, does not come without a cost. In the initial stages of the original development of an electronic students records system for the University of the Philippines, dubbed as SRS, the concern was to create a functioning user friendly conversion of the current manual system. The primary design required a swift deployment. Thus the choice of platform was decided and was, unfortunately, a proprietary system. A system deemed sufficient albeit expensive. An expense that was eventually reconsidered with the advent of the open source paradigm, hailed as the means to free businesses and individuals from the shackles of a tight-gripping proprietary system. The Computerized Registration System 2.0 is a Java-based web application which automates the registration process using the new open source technologies, JasperReports, Struts, and PostgeSQL. The primary objectives of CRS 2.0 is very much with the objectives of the current CRS to automate the tasks in the registration process.